2017
DOI: 10.1002/jemt.22829
|View full text |Cite
|
Sign up to set email alerts
|

Influence of passive ultrasonic irrigation on the efficiency of various irrigation solutions in removing smear layer: a scanning electron microscope study

Abstract: To evaluate the influence of passive ultrasonic irrigation (PUI) to remove the smear layer with different irrigation solutions. Seventy-eight single rooted mandibular premolars were used. The working lengths were measured and the root canals were prepared by using nickel titanium rotary files. The specimens were subjected to six different irrigation regimens: sodium hypochloride (NaOCl) with classic irrigation (CI); NaOCl with PUI; EDTA with CI; EDTA with PUI; QMix with CI; and QMix with PUI. The specimens wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
14
0
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 27 publications
5
14
0
8
Order By: Relevance
“…Some studies have demonstrated that the use of a chelating solution alone has limited capacity for removing the smear layer and debris present in the canals after RCP. 15,22,23 These findings partly corroborated those of the present study; however, the results here found pointed out significant advantage of the use of activation methods, more specifically in cleaning the apical thirds and in more widened canals. In the case of the less widened canals, no cleaning method, whether the use of EDTA solely, or by means of its activation, was able to produce results similar to those offered by C+.…”
Section: Discussionsupporting
confidence: 91%
“…Some studies have demonstrated that the use of a chelating solution alone has limited capacity for removing the smear layer and debris present in the canals after RCP. 15,22,23 These findings partly corroborated those of the present study; however, the results here found pointed out significant advantage of the use of activation methods, more specifically in cleaning the apical thirds and in more widened canals. In the case of the less widened canals, no cleaning method, whether the use of EDTA solely, or by means of its activation, was able to produce results similar to those offered by C+.…”
Section: Discussionsupporting
confidence: 91%
“…Although SEM evaluation is known for being subjective due to its dependency on operator, to minimize this observer bias, SEM images were obtained from equidistant points of each root canal third similar to previous studies (Ayranci et al, ; Zhu et al, ). Despite the fact that SEM images are obtained at different magnifications in our study, observers scored SEM images at 1000× magnification similarly to several previous studies (Arslan et al, ; Castagna et al, ; Kocak et al, ; Sahar‐Helft et al, ; Turkel et al, ; Zhu et al, ). It is well known that smear‐free dentin regions are selected by SEM operators (Hülsmann, Peters, & Dummer, ).…”
Section: Discussionmentioning
confidence: 52%
“…Despite the fact that SEM images are obtained at different magnifications in our study, observers scored SEM images at 1000× magnification similarly to several previous studies Castagna et al, 2013;Kocak et al, 2017;Sahar-Helft et al, 2015;Turkel et al, 2017;Zhu et al, 2013). It is well known that smear-free dentin regions are selected by SEM operators (Hülsmann, Peters, & Dummer, 2005).…”
Section: Discussionmentioning
confidence: 82%
“…O mesmo foi encontrado, em um estudo comparando a eficácia de diferentes soluções irrigadoras quando da irrigação clássica com seringa e irrigação passiva ultrassô-nica (PUI). Os resultados demonstraram que PUI aumentou a capacidade de remoção de smear layer, para todas soluções avaliadas, inclusive o EDTA, quando comparado à irrigação clássica 58 . Trabalhos [59][60][61] registraram que tanto o EDTA, EDTA-T e o ácido cítrico foram eficazes quando usados em menor espaço de tempo, sem contudo, causar danos a estrutura dentinária.…”
Section: Discussionunclassified
“…Uma nova proposta de ativação do EDTA, por meio da utilização de LASER de baixa potência, também foi avaliada 27,58,[65][66][67][68][69] . Verificou-se que o uso de LA-SER de diodo de baixa potência associado ao EDTA e ao NaOCl diminuíram a quantidade de smear layer, de todas as paredes do canal radicular.…”
Section: Discussionunclassified